(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
The main causes of death from diseases of the circulatory system are coronary heart disease and cerebrovascular diseases; their total contribution to mortality in men and women is 82.3% and 85.8%, respectively. It is generally accepted that the high prevalence of diseases of the circulatory system is due to both hereditary factors and lifestyle characteristics: smoking, unhealthy diet, low physical activity, alcohol abuse, which lead to a high prevalence of arterial hypertension (AH), hypercholesterolemia, diabetes mellitus (DM) among the population and obesity , contributing to the development and progression of major diseases of the circulatory system. The basis of most diseases of the circulatory system is atherosclerosis, which is asymptomatic for many years and, as a rule, is quite pronounced by the time clinical symptoms appear. One of the main characteristics of atherosclerosis is the multifocality of the lesion with the simultaneous involvement of one or more vascular beds. Combined forms of atherosclerosis with damage to the coronary, carotid and peripheral arteries are established in 30–65% of cases. The main causes of death from diseases of the circulatory system are coronary heart disease and cerebrovascular diseases ; their total contribution to mortality in men and women is 82.3% and 85.8%, respectively. It is generally accepted that the high prevalence of CSD is due to both hereditary factors and lifestyle characteristics: smoking, unhealthy diet, low physical activity, alcohol abuse, which lead to a high prevalence of arterial hypertension , hypercholesterolemia, diabetes mellitus and obesity, contributing to the development and progression of major diseases of the circulatory system. The basis of most diseases of the circulatory system is atherosclerosis, which is asymptomatic for many years and, as a rule, is quite pronounced by the time clinical symptoms appear. One of the main characteristics of atherosclerosis is the multifocality of the lesion with the simultaneous involvement of one or more vascular beds. Combined forms of atherosclerosis with damage to the coronary (CA), carotid (CA) and peripheral arteries (PA) are established in 30–65% of cases.